Optimizing the Inspectorate's Supervisory Function to Achieve Accountability in Regional Financial Management in Kuantan Singingi Regency - Nurcahyani, Rifki; Muhammad, Hasman (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This study aims to analyze the role of the Regional Inspectorate of Kuantan Singingi Regency in overseeing regional financial management. The background of the research reflects the importance of internal guidance and supervision as an integral part of local government management to achieve good and clean governance. The main objective of this research is to understand the main tasks and functions of the Inspectorate and its impact on the accountability of regional financial management at the district level. This research uses a qualitative approach with a literature review design. Data were collected through literature analysis from academic journals, books, research reports, and official documents related to inspectorates, governance, and local financial management. Data analysis was conducted by reviewing literature categorized based on key themes, such as local financial supervision and accountability, governance, and the duties of the Inspectorate. The results show that the Regional Inspectorate of Kuantan Singingi Regency has a central role in overseeing development in the region. Its main tasks involve the formulation of technical policies, internal supervision, and the implementation of special supervision. However, there are obstacles such as a lack of human resources and infrastructure, which affect the optimality of supervision of local finances.